(untitled) (Cadernos de Sociomuseologia, 2017)
This paper deals with two key issues in the study of the work of kinetic Latin-American artist Jesús Soto (1923-2005): the use of combinatorial methods to generate new schemes for structuring the image, renouncing to traditional concepts of harmony and composition, and the incorporation of random elements in the configuration of his works, with the purpose of multiplying ad infinitum the possibilities of their performance. The analysis of the artist production allowed us to recognize the repetition, the permutation and the freedom of action as fundamental ideas in the process of formal and conceptual configuration of his works. In this way, spectator and work of art act as a unit whose dynamism is only a portion of a much broader physical domain. Keywords: Latin-American art, kinetic art, art and mathematics, Jesús Soto.